Exploring The Factors Influencing The Intentions to Become A Rural Bank Customer in Jakarta Central Market - Andi Muhammad Sadat; Sholikhah; Basrah Saidani (PT FORMOSA CENDEKIA GLOBAL, 2021)
Retaining existing customers and obtaining potential new customers are the critical success factors for an enterprise. Therefore, choosing the target market and allocating organizational resources to support them are essential. As a bank with unique customer characteristics, the rural banks (Bank Perkreditan Rakyat/BPR) should pay attention to external and internal factors. This study intends to explore what factors influence the Intention to become BPR’s customers. First, this research took 200 respondents who worked in seven central markets in Jakarta with a quota sampling approach to complete the questionnaire whose indicators were obtained from FGD (focus group discussion) and prior research. Data were analyzed by applying factor analysis techniques and linear regression by SPSS 24. The results show that factors, namely Attitude and Control over behavior, proved to have a positive correlation toward Intention, while Subjective norm affects negatively. Conclusion and suggestions for future study are provided.